High intravascular tissue factor—but not extracellular microvesicles—in septic patients is associated with a high SAPS II score. Issue 1 (December 2016) - Trepesch, Carolin; Nitzsche, Ramona; Glass, Aenne; Kreikemeyer, Bernd; Schubert, Jochen; Oehmcke-Hecht, Sonja
Abstract Background Sepsis is associated with coagulation abnormalities, and a high content of intravascular tissue factor (TF) may contribute to the development of multisystem organ failure. Circulating microvesicles (MVs) are increased during sepsis and characterized by their phosphatidylserine content. It is unclear whether MVs—as a part of the host response to the infection—are beneficial or rather contribute to systemic complications in sepsis. In the present prospective clinical pilot study, we investigated whether plasma TF and MVs are associated with the risk of multiple organ failure and mortality. Methods Thirty patients diagnosed with sepsis, severe sepsis, or septic shock were enrolled and classified as 19 survivors and 11 non-survivors. Blood samples were collected on the day of admission and then daily for up to 2 weeks. MVs and TF were quantified in plasma by ELISA. Results Non-survivors had significantly higher TF concentrations on day 3 compared to survivors. Logistic regression analysis revealed that patients with high amounts of TF had significantly increased risk for severity of disease, according to high Simplified Acute Physiology Score II (SAPS II) scores (odds ratio 18.7). In contrast, a higher content of phosphatidylserine-rich MVs were apparently associated with a lower risk for mortality and multiple organ failure, although this was only a trend and the odds ratios were not significant. Conclusions This study showed that a high amount of TF in septic patients is significantly associated with increased risk for disease severity, according to a high SAPS II score. Quantification of total MVs in plasma, independent from their cell origin, might be indicative for the outcome of patients in sepsis.